Corpus Callosum Hematoma in a 4-Year-Old Child Following Road Traffic Accident. A Case Report - Gazeti, Hind; Elfituri, Zinab; Algrmi, Sufwan (Libyan Journal of Public Health Practices, 2024)
A 4-year-old male child presented to the emergency department at Nawat Al Mustaqbal Hospital in Zawia City, following a head injury sustained in a road traffic accident (RTA). During the initial brain CT scan, a corpus callosum hematoma was detected in the interhemispheric fissure, initially thought to be a traumatic subarachnoid haemorrhage (tSAH). A follow-up brain CT conducted six hours later showed no additional abnormal findings. Subsequently, the patient was transferred to the surgical department for conservative treatment. Following a three-day improvement in his condition, he was discharged. Optimal management for corpus callosum hematoma includes good supportive care, careful clinical follow-up, and prompt recognition of delayed complications to achieve the best neurological outcome